The use of monocyte to HDL ratio to predict postoperative atrial fibrillation after aortocoronary bypass graft surgery - Tekkesin, Ahmet Ilker (North Clin Istanb, 2017)
OBJECTIVE: Postoperative atrial fibrillation (POAF) is a frequent and serious complication after aortocoronary bypass graft (ACBG) surgery and one that, unfortunately, increases morbidity and mortality. Postoperative stroke, hemodynamic instability, renal failure, infection, need for inotropic agent and coronary unit are complications caused by POAF. Inflammation and oxidative stress are among several mechanisms that contribute to pathogenesis of POAF. Monocyte to HDL (M/H) ratio is a newly defined parameter of both inflammation and oxidative stress. In this study, M/H ratio was investigated as predictor of POAF after ACBG surgery. METHODS: Total of 311 patients who underwent ACBG surgery were included in the study. Blood samples for analysis of routine biochemistry and lipid panel were obtained from the patients on the morning of ACBG surgery after 12 hours of fasting. Patients were continuously monitored for occurrence of POAF throughout hospitalization. RESULTS: POAF was observed in 71 patients following ACBG operation. M/H ratio was significantly higher in POAF(+) group compared with POAF(-) group (p<0.001). Median age of POAF(+) patients was 62.0±10.1 years, which was significantly higher than mean age of POAF(-) patients. Other atrial fibrillation (AF) risk factors, such as hypertension, diabetes mellitus, smoking, and alcohol consumption, were similar between groups. Potassium level was statistically lower in POAF(+) group compared with POAF(-) group (p=0.01). CONCLUSION: M/H ratio is an indicator of inflammation and oxidative stress, both of which play important role in pathogenesis of AF. M/H ratio was found be statistically significantly higher in POAF(+) patients than in POAF(-) patients.